THE IMPACT OF PROVIDING APPRECIATION STARS “DIARY OF MY BONE” ON CHILDREN’S EMOTIONAL WELL-BEING IN MALANG REGENCY VILLAGE - Sari, Herdyana Lintang; Anwar, Mochamad Saiful (Poltekkes Kemenkes Jakarta III, 2025)
Children’s mental health is essential for their emotional, social, andacademic development. Anxiety and other mental disorders can hinder achild's future, making early intervention crucial. Diary of My Bone is acompanion journal designed for children aged 7-11, structured according toErik Erikson’s developmental stages. It introduces kyphosis through simpleexplanations and illustrations while providing guidance on brace care. Thejournal encourages children to track daily activities, emotions, food intake,and brace usage, with star stickers as motivation. This study examines theimpact of Diary of My Bone on children’s moods using a pre-test and posttest experimental design without a control group. The research wasconducted in Sumber Sekar Village, Malang Regency, with a minimum of 10children meeting inclusion criteria. Mood assessments were conducted beforeand after a four-week intervention, and data were analyzed using a paired ttest. Results show that the use of Diary of My Bone significantly improvedchildren’s moods, enhancing their social interactions, confidence, andoverall happiness. The star sticker reward system effectively motivatedchildren to complete their daily tasks, fostering emotional resilience and selfdiscipline. These findings highlight the potential of appreciation-basedinterventions in nursing practices to support children's psychological wellbeing. Integrating simple reward-based strategies into pediatric healthcarecan enhance children’s motivation, emotional expression, and adherence tohealth routines, offering a cost-effective approach to long-term healthmonitoring and development.